MRNA sequencing of novel cell lines from human papillomavirus type‐16 related vulval intraepithelial neoplasia: Consequences of expression of HPV16 E4 and E5. Issue 9 (5th June 2014) - Bryant, Dean; Onions, Tiffany; Raybould, Rachel; Flynn, Áine; Tristram, Amanda; Meyrick, Sian; Giles, Peter; Ashelford, Kevin; Hibbitts, Samantha; Fiander, Alison; Powell, Ned
<x xml:space="preserve">Abstract</x> Vulval intraepithelial neoplasia is a precursor of vulval cancer and is commonly caused by infection with Human Papillomavirus (HPV). Development of topical treatments for vulval intraepithelial neoplasia requires appropriate in vitro models. This study evaluated the feasibility of primary culture of vulval intraepithelial neoplasia biopsy tissue to produce cell lines for use as in vitro models. A potentially immortal cell line was produced which gave rise to three monoclonal lines. These lines were characterized for HPV genomic integration and for viral gene expression using ligation‐mediated PCR and quantitative PCR. Distinct patterns of viral integration and gene expression were observed among the three lines. Integration and expression data were validated using deep sequencing of mRNA. Gene ontology analyses of these data also demonstrated that expression of the HPV16 E4 and E5 proteins resulted in substantial changes in the composition of the cell membrane and extracellular space, associated with alterations in cell adhesion and differentiation. These data illustrate the diverse patterns of HPV gene expression potentially present within a single lesion. The derived cell lines provide useful models to investigate the biology of vulval intraepithelial neoplasia and the interactions between different HPV gene products and potential therapeutic agents. J. Med. Virol. 86:1534–1541, 2014. © 2014 Wiley Periodicals, Inc.